2017
DOI: 10.1093/fampra/cmw134
|View full text |Cite
|
Sign up to set email alerts
|

Amitriptyline for musculoskeletal complaints: a systematic review

Abstract: Few studies have evaluated the use of amitriptyline in musculoskeletal complaints. Although amitriptyline may be effective in musculoskeletal complaints, more studies are required to establish for whom amitriptyline works better than other analgesics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Those ADRs are linked with TCAs mechanism in muscarinic cholinergic receptors [12,31]. The result of our study is in line with some systematic reviews [30,32,33]. A systematic review suggests strong evidence regarding dry mouth and constipation as ADRs of amitriptyline and desipramine, also constipation, insomnia, and drowsiness as ADRs of nortriptyline [32].…”
Section: Discussionsupporting
confidence: 90%
“…Those ADRs are linked with TCAs mechanism in muscarinic cholinergic receptors [12,31]. The result of our study is in line with some systematic reviews [30,32,33]. A systematic review suggests strong evidence regarding dry mouth and constipation as ADRs of amitriptyline and desipramine, also constipation, insomnia, and drowsiness as ADRs of nortriptyline [32].…”
Section: Discussionsupporting
confidence: 90%
“…Clinical evidence suggests that dual antidepressants provide better analgesic efficacy in chronic neuropathic pain. In this regard, the analgesic efficacy of amitriptyline (a tricyclic antidepressant -TCA) is the bestdocumented in complex regional pain syndrome, neuropathic and musculoskeletal pain, and fibromyalgia (Wiffen et al, 2013;Moore et al, 2015;Brown et al, 2016;van den Driest et al, 2017). However, due to the side effects of TCAs, the SNRI duloxetine has been the first choice treatment for peripheral diabetic neuropathic pain and fibromyalgia, with a good safety profile.…”
Section: Clinical Approachmentioning
confidence: 99%
“…The assessments of the methodological quality are given in Tables 2 and 3. Out of 25 included studies, 11, 9 and 5 studies were classified as high [2,14,16,17,33,34,37,41,44,45,48] moderate [12,35,36,42,43,47,49] and low [32,[38][39][40]46] quality, respectively. Table 3 shows the results of the methodological quality assessment according to each item.…”
Section: Assessment Of Methodological Quality Of Included Srsmentioning
confidence: 99%
“…Most SRs and MAs in this area, illustrated that there was no clear evidence of ADs effectiveness on LPB [2,16,34,41,[54][55][56] while others achieved contradictory results [18,35,36,57,58]. Some of them showed that TCAs had significant analgesic effect more than other types of Ads [15,17,32,40,42,[59][60][61][62], while there exists contradiction as well [63]. In addition, some reviews reported a lack of sufficient data for the conclusion [33,55,64].…”
Section: Summary Of Ads Effect On Lbpmentioning
confidence: 99%
See 1 more Smart Citation